Healthcare Workers Infected with COVID-19 in a Tertiary Care Center, Kerala, India - Sahya S. Dev; Joe Abraham; Abraham Varghese V. (Research Highlights in Disease and Health Research Vol. 8, 2023)
This study describes the characteristics of healthcare workers who tested positive for COVID-19 in a tertiary care hospital in India. Healthcare workers (HCW) are at high risk of acquiring infections during novel disease outbreaks, especially before the transmission dynamics are fully outlined. Therefore, it is critical to investigate the prevalence and risk factors among HCWs. A descriptive cross-sectional study was conducted between 22 July 2020 and 31 January 2021 in a 900-bed tertiary hospital in South Kerala, India. The study was conducted among HCWs from a tertiary care centre with a real-time polymerase chain reaction (RT-PCR) test positive for COVID-19 on a nasopharyngeal swab. All healthcare workers with confirmed SARS-CoV-2 infections were contacted over the telephone to collect data regarding their probable source of contact, usage of personal protective equipment,and clinical course. Their treatment history was extracted using electronic health records. During the study period, 192 HCWs were RT-PCR positive for COVID-19.The mean age of the study participants was 34.01 years. Among the infected, 23.4% were male employees, while the remaining 76.6% were female employees. Nurses were most commonly affected (36.5%), followed by doctors (22.9%) and housekeeping staff (15.6%). Healthcare workers experience an increased risk of COVID-19 infection not only due to their close contact with highly infectious patients,but also through exposure to undiagnosed or subclinical infectious cases.Protection of HCWs from infection is critical for the resilience of the health system now tasked with facing a major pandemic like COVID-19. Infected HCWs acquired the infection from the hospital in 73.4% of cases,while 38.6% had direct contact with patients or colleagues. Ensuring the willingness of health care workers to work in designated COVID-19 wards is essential. Trust in being protected is the strongest factor influencing the motivation of health workers during a pandemic. HCWs are at increased risk of healthcare-associated infections due to the frontline nature of their work.